Determinants Of Foreign Direct Investment Inflows in Afghanistan - Mohammad Bilal Tayeb, Bharti Wadhwa (International Journal of Modern Agriculture, 2020)
The objective of this study is determining the impact of several factors like inflation, exchange rate, unemployment, government expenditure and economic growth on FDI (Foreign Direct Investment) attraction in Afghanistan. In this paper secondary data, the period from 2005 to 2017 has been used for statistical & econometrical analysis. Empirical analysis & estimation has been performed by analytical tools of regression. In addition, Augmented Dickey Fuller (ADF) test & Pillips-Perron (PP) test is used for time series data analysis which are derived from WDI. In the result of this study it was found that the unemployment in Afghanistan is statistically significant factor having positive relationship with FDI or contributing positive impact to the attraction of FDI in Afghanistan and economic growth are statistically insignificant factor with a positive contribution to the attraction of FDI in Afghanistan although, the inflation, exchange rate and government expenditure are also statistically significant with negative sign. This paper using data from 2005-2017, a time series data estimator suggested that the inflation, government expenditure, exchange rate, unemployment and economic growth are the main determinants of FDI inflows in Afghanistan.